Repetitive transcranial magnetic stimulation of the supplementary motor area (SMA) degrades bimanual movement control in humans. - Serrien, D; Strens, L; Oliviero, A; Brown, P (2002)
Moving the upper limbs at a common tempo according to an in-phase or anti-phase mode represents elementary coordination dynamics. Previously, the role of the supplementary motor area (SMA) has been emphasized for successful production of these patterns. The objective of this study was to investigate whether repetitive transcranial magnetic stimulation (rTMS) of the SMA at 5 Hz can interfere with these isofrequency configurations in the post-stimulation stage. Results showed a deterioration of temporal control as a function of coordinative complexity. This effect was associated with a decrease in the functional coupling between the primary motor cortices, as measured by electroencephalographic coherence. These data suggest that rTMS of the SMA can modify interhemispheric communication and accordingly modulate interlimb behavior.